ANALISIS PENGARUH ELECTRONIC WORD OF MOUTH (e-WOM) TERHADAP CITRA DESTINASI, KEPUASAN WISATAWAN, DAN LOYALITAS DESTINASI PERKAMPUNGAN BUDAYA BETAWI (PBB) SETU BABAKAN JAKARTA SELATAN - Salman Paludi (Panorama Nusantara, 2016)
The development of internet users in Indonesia lately increased rapidly resulting effect great change for someone to convey the message or information to others. The widespread use of social networking sites to make the deployment of an information or news by word of mouth via the Internet (e-WOM) is widespread, including information about an attraction information, such as the Setu Babakan in South Jakarta. From previous studies, such as Putu Yudi Setiawan (2014), Geng-Qing Christina Chia, Hailin Qu (2008) and Zarrad H and Debabi M. (2015) diketahu that there pengarun of-variables such as e-WOM, Citra destinations , tourist satisfaction and destination loyalty. With 280 sample data visitor and using SEM as a tool of analysis can be seen that in the attraction Setu Babakan there is a significant positive effect between e-WOM with Citra destinations, image destinations positive effect on satisfaction rating, and image destinations also affect positive on Loyalty destinations. Meanwhile between e-WOM variable with traveler satisfaction and traveler satisfaction to destination loyalty has no effect.